Grounded theory research. (4th November 2014) - Mishra, Pavitra; Gupta, Rajen; Bhatnagar, Jyotsna
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the phenomenon of work-to-family enrichment in totality. Using grounded theory, the study aims to understand antecedents, moderators, and consequences of work-to-family enrichment. This study also investigates strategies adopted by individuals to enhance their work-family enrichment experience. Design/methodology/approach – The paper opted for an exploratory study using the open-ended approach of grounded theory. This paper builds a model to understand the phenomenon by applying Strauss and Corbin's (1990) "paradigm model" approach of grounded theory. The paper throws light on the key tenets of grounded theory research and explains use of grounded theory as a rigorous method for business research. Data were collected by taking 24 in-depth interviews with employees representing middle management segment of consulting, IT and FMCG firms in India. Findings – This study reports "perceived work-family culture" of an organization as an antecedent of "work-to-family enrichment." It also finds "community resources" and "family role salience" as significant contributors in enriching the experience of professionals. Work-to-family enrichment experience has positive influence on "employer brand attraction" and "organizational citizenship behavior" and has negative influence on "intention to quit." The study has also added to the literature by identifying Psychological Capital as one of the consequences. The study has highlighted segmentation, i.e. by maintaining work and family boundaries, support from extended family members or close friends, engaging in activities that provides happiness and personal peace like being a part of NGO, time management and scheduling, engaging in shopping and availing community facilities like good day cares as major strategies used by Indian professionals to enhance their work-to-family enrichment. Research limitations/implications – The study demonstrates application of grounded theory for understanding a phenomenon holistically. It is one of its kinds of study conducted to understand work-to-family enrichment. Practical implications – This is a unique study, where attempts have been made to understand and integrate work-to-family enrichment phenomenon in totality. The paper provides insights to the managers about the importance of suitable work-family culture and other factors to ensure successful implementation of work-family policies. The paper also identifies strategies adopted by individuals to attain work-family enrichment. Social implications – Demographic shifts, changing market and economic trends, technological advances and competitive forces have made work-family interface an important issue for both academicians and practitioners. In India, these changes can be experienced in terms of demographic profile of work force. Changes in the definitions of work and family, shifting family structure, changing profile of work (due to technological advancement, women empowerment, etc.) are transforming the work-family interactions in emerging economies. According to Hewitt's Attrition and Retention Asia Pacific Study, the need for a balance between work and personal life has become an integral element of employee's expectations from their work organization. Originality/value – This paper fulfils an identified need to study and explore positive side of work-family interface especially in emerging economies like India. This is the first attempt to study the relationships in the work-family domain from a grounded theory approach in Indian context and probably one of the first few in the literature.